Measurements of the time evolution of coherent excitation - Camp, Howard Alan (Kansas State University, 2005)
In recent years, coherent excitation techniques have focused on the ability to efficiently prepare atomic or molecular systems into a selected state. Such population control plays a key role in cutting-edge research taking place today, such as in the areas of quantum information and laser-controlled chemical reactions. Stimulated Raman adiabatic passage (STIRAP) is a widely-used coherent excitation technique that provides a relatively robust control mechanism for efficiently exciting a target population into a desired state. While the technique is well proven, current experimental techniques yield little information on the population dynamics taking place throughout the excitation process, and experimentalists rely solely on final excited-state measurements to determine the efficiency of population transfer. This dissertation presents a unique diagnostic tool to measure multilevel coherent population transfer on a short (nanosecond) timescale. The technique described here uses magneto-optical trap recoil ion momentum spectroscopy (MOTRIMS) as a noninvasive probe of a coherently-controlled system. It provides extremely detailed information about the excitation process, and highlights some important characteristics seen in excited populations that would otherwise be misleading or completely overlooked if one were to use more traditional diagnostic techniques. This dissertation discusses both the theoretical and experimental results applied to three-level coherently excited target populations of Rb-87.
Keywords: Coherent excitation; Time evolution; STIRAP; Stimulated Raman adiabatic passage; MOTRIMS; Magneto-optical trap recoil ion momentum spectroscopy; COLTRIMS; Physics, Atomic (0748); Physics, Molecular (0609); Physics, Optics (0752)